Analysis on the Spatiotemporal Characteristics of the Postearthquake Reconstruction Efficiency of the Extremely Earthquake-Stricken Areas by the Wenchuan Earthquake Based on the DEA-Malmquist Index. (19th October 2020) - Lv, Pin; Liu, Bin; Yuan, Mingkang; Han, Suyue; Zhang, Di; Zhang, Lv
Abstract : The Wenchuan earthquake, which occurred on May 12, 2008, caused a large number of casualties and substantial property losses. Postearthquake reconstruction is a complex and systematic project, the core of which is to enable the residents of the earthquake-stricken areas to resume normal productivity and life as soon as possible. This paper aims to evaluate the efficiency of postearthquake reconstruction in extremely earthquake-stricken areas. From the perspective of the inputs and outputs, the DEA-Malmquist index was used to construct a reconstruction efficiency evaluation model for the extremely stricken areas. Reconstruction efficiencies are analyzed for 10 areas that were severely impacted by the Wenchuan earthquake. Finally, three major disaster-pregnancy environmental factors, namely, including topography, fault zones, and river systems, are selected. Based on the temporal trend of reconstruction efficiency, the degree of correlation between the postearthquake reconstruction efficiency fluctuation and the three major disaster-pregnancy environmental factors is analyzed. The study results show that the overall reconstruction efficiency of the 10 extremely earthquake-stricken areas was relatively high. In 2011, the reconstruction efficiency basically returned the areas to preearthquake levels, and there was a small fluctuation in efficiency due to the effects of earthquake-induced hazards and the reduction of external forces. Spatially, the reconstruction efficiencies of the 10 extremely stricken areas do not show a "convergence effect, " and the reconstruction efficiencies were closely related to the characteristics of the resources in the extremely stricken areas. In terms of the main disaster-pregnancy environment, the terrain complexity is most closely related to fluctuation of reconstruction efficiency, with a correlation coefficient of 0.9975, followed by river network density and the lowest fault density. Therefore, to improve the reconstruction efficiency of the extremely earthquake-stricken areas, the adjustment measures that promote local advantages should be fully utilized to mitigate the lasting effects of earthquake-induced hazards.